Math

posted by .

Simplify the expression and combine like terms

-5(4y-7) + 4(2y+5)

  • Math -

    first use the distributive property to multiply the terms out:
    -20 y + 35 + 8 y + 20
    you now have 8-20 y's
    which is -12 y
    and you have the numbers 35+20 which is 55
    so the result is
    55 - 12y

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    i don't know how to do this with the fractions. can you please please help?
  2. Math

    Simplify the expression and combine like terms. How i do this?
  3. math

    Simplify and combine the like terms: 2f + 7g - 6 + 8g
  4. 4-- math questions

    1. Simplify this expression: 6d + 11 – 3d + 4. 3d 17d + 7d 3d + 15 9d + 15 2. Name the coefficients in this expression: 7a + 3b + 9. 7 and 3 7, 3, and 9 7a and 3b 7a, 3b, and 9 3. Name the like terms in this expression: 4c + 12 + …
  5. Alg1

    Given 4√50 - 2√8 observe that √50 =√25*2 and √8=√4*2 and that 25 and 4 are perfect squares, so I simplify the expression to 100√2 - 8√2 I can then combine these terms to get 92√2 …
  6. math

    could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17
  7. math

    could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17
  8. Math I'm DYING!!!

    1. y - 5/3 =1 2. Combine like terms: -21a + 16a 3. Simplify the expression: 9a - b - 2a - 10b 4. 5(x + 10) + x 5. -4n + 7 + 2n = 1 Thanks for everything!!
  9. Math

    Combine like terms to simplify the expression. 1/_4+6+9y= Answer: 5y+6 2/ 20a+7+3= Answer: 20+10 3/_5k+9_2+9k= Answer: 4k+7 4/ 17+2.9h+3= Answer: 30+14 Simplify the expression. 5/ _4(3+d)+7d_d= Answer: _16+6d 6/ 8+5(j_5)+3j_1= Answer: …
  10. math

    10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12?

More Similar Questions